Galangin: A metabolite that suppresses anti-neoplastic activities through modulation of oncogenic targets. Issue 4 (February 2022) - Tuli, Hardeep Singh; Sak, Katrin; Adhikary, Shubham; Kaur, Ginpreet; Aggarwal, Diwakar; Kaur, Jagjit; Kumar, Manoj; Parashar, Nidarshana Chaturvedi; Parashar, Gaurav; Sharma, Uttam; Jain, Aklank
With the dramatic increase in cancer incidence all over the world in the last decades, studies on identifying novel efficient anti-cancer agents have been intensified. Historically, natural products have represented one of the most important sources of new lead compounds with a wide range of biological activities. In this article, the multifaceted anti-cancer action of propolis-derived flavonoid, galangin, is presented, discussing its antioxidant, anti-inflammatory, antiproliferative, pro-apoptotic, anti-angiogenic, and anti-metastatic effects in various cancer cells. In addition, co-effects with standard chemotherapeutic drugs as well as other natural compounds are also under discussion, besides highlighting modern nanotechnological advancements for overcoming the low bioavailability issue characteristic of galangin. Although further studies are needed for confirming the anti-cancer potential of galangin in vivo malignant systems, exploring this natural compound might open new perspectives in molecular oncology.